PENGARUH JUMLAH PENDUDUK, RATA-RATA LAMA SEKOLAH (RLS), TENAGA KERJA DAN PERTUMBUHAN EKONOMI TERHADAP JUMLAH PENGANGGURAN DI KABUPATEN TANA TORAJA - Restin sampe Mantun; Anderson G. Kumenaug; Wensy F.I Rompas (PT. Hasba Edukasi Mandiri, 2025)
Tana Toraja Regency is an area located in the province of South Sulawesi which still faces issues related to employment, especially unemployment. Tana Toraja is a Regency with an unemployment rate ranked sixth in South Sulawesi. This study aims to analyze the effect of population, Average Years of Schooling (ADL), Labor, and Economic Growth on the Number of Unemployed in Tana Toraja Regency. The data used in this study are secondary data obtained from the Central Statistics Agency. The analysis was carried out using multiple linear regression with the Ordinary Least Square (OLS) method through Eviews 12 software. The results of the study showed that the number of residents has a negative and significant relationship to the number of unemployed, indicating that an increase in the number of residents is accompanied by a decrease in the number of unemployed. Average Years of Schooling (ADL) has a positive and significant relationship, interpreted that the higher the average years of schooling, the number of unemployed increases. Labor has a negative relationship but does not have a significant effect, indicating that an increase in the number of workers tends to be followed by a decrease in the number of unemployed. Meanwhile, Economic Growth has a positive and significant relationship, indicating that increasing economic growth is followed by an increase in the number of unemployed. These three variables together have a significant relationship with the number of unemployed in Tana Toraja Regency.